2020
DOI: 10.1021/acs.langmuir.9b03722
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Polymer Micelles with Dual Conjugation of Doxorubicin and Curcumin: Synergistically Enhanced Efficacy against Multidrug-Resistant Tumor Cells

Abstract: This paper reports a novel redox-sensitive micellar system for the co-delivery of doxorubicin (Dox) and a chemosensitizer (curcumin, Cur) to overcome the multidrug resistance (MDR) in cancer cells. Dox and Cur were co-conjugated onto a zwitterionic polymer, poly(carboxybetaine) (pCB), to form Cur-pCB-Dox that self-assembled into stable micelles (164.2 ± 4.8 nm). Single-drug conjugates (pCB-Dox and pCB-Cur) were prepared for comparisons. Compared to the high half-maximal inhibitory concentration (IC 50 ) of Dox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 72 publications
1
21
0
1
Order By: Relevance
“…These studies demonstrate that drug transporters participate in DOX resistance and they are potential targets of curcumin in providing chemosensitivity. As an example, it was shown that colocal delivery of DOX and curcumin can synergistically increase the effectiveness toward multidrug-resistant cancer cells, e.g., further reducing the IC 50 value by 37% (8.9 µg/mL; Figure 2) [139]. The nanosized feature of the zwitterionic antifouling micelles and endocytic pathway to bypass P-gp-mediated drug efflux led to high cellular uptake of the conjugated drugs that were released in the tumor cells of high GSH concentration.…”
Section: Curcumin In Reversing Dox Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…These studies demonstrate that drug transporters participate in DOX resistance and they are potential targets of curcumin in providing chemosensitivity. As an example, it was shown that colocal delivery of DOX and curcumin can synergistically increase the effectiveness toward multidrug-resistant cancer cells, e.g., further reducing the IC 50 value by 37% (8.9 µg/mL; Figure 2) [139]. The nanosized feature of the zwitterionic antifouling micelles and endocytic pathway to bypass P-gp-mediated drug efflux led to high cellular uptake of the conjugated drugs that were released in the tumor cells of high GSH concentration.…”
Section: Curcumin In Reversing Dox Resistancementioning
confidence: 99%
“…Cur: curcumin; Dox: doxorubicin; MDR: multidrug resistance; pCB: poly(carboxybetaine). Addapted with permission from [139].…”
Section: Curcumin In Reversing Dox Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric micelles (PMs) have gathered significant interest as DDS because of their low toxicity, good biocompatibility, modified release pattern, increased blood circulation time, and ability to solubilize hydrophobic drugs such as CUR in the micelles' core (Akbar et al, 2018). The hydrophobic segments in the polymers/copolymers form the micelle core that acts as a reservoir for hydrophobic drugs, while the hydrophilic headgroups form the micellar shell that can improve the colloidal stability and prevent protein adsorption, thus prolonging the circulation time (Gou et al, 2011;Zhao et al, 2020). In particular, one type of material that is used as a biocompatible complexing agent to improve the water solubility, stability, and bioavailability of poor aqueous soluble drugs is Pluronic ® copolymers, which contain hydrophobic poly(propylene oxide) (PPO) blocks and hydrophilic poly(ethylene oxide) (PEO) blocks arranged in a triblock structure, PEO-PPO-PEO.…”
Section: Micellesmentioning
confidence: 99%
“…Jiang's group [23][24][25] has prepared several polymers (such as PCBMA, PSBMA and PMPC), which exhibited excellent stability and antifouling properties in vivo. Meanwhile, it has been reported that the cellular uptake efficiency of Molecules 2021, 26, 5274 2 of 8 micelles would be increased by the modification of a zwitterionic segment in tumor tissues [26,27]. The main reason is the difference in pH between normal tissue cells (pH = 7.4) and tumor tissue (acidic).…”
Section: Introductionmentioning
confidence: 99%